2003
DOI: 10.1021/jm030933g
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors of the Plasmodium falciparum Enzymes Plasmepsin I and II Devoid of Cathepsin D Inhibitory Activity

Abstract: The hemoglobin-degrading aspartic proteases plasmepsin I (Plm I) and plasmepsin II (Plm II) of the malaria parasite Plasmodium falciparum have lately emerged as putative drug targets. A series of C(2)-symmetric compounds encompassing the 1,2-dihydroxyethylene scaffold and a variety of elongated P1/P1' side chains were synthesized via microwave-assisted palladium-catalyzed coupling reactions. Binding affinity calculations with the linear interaction energy method and molecular dynamics simulations reproduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(162 citation statements)
references
References 46 publications
(140 reference statements)
6
155
1
Order By: Relevance
“…15 The best IC 50 value for the inhibition of P. falciparum was 0.4 µM, thus achieving a remarkable improvement with respect to other inhibitors of PLM II. [8][9][10][11] We also demonstrated that the removal of the Lys-PQ moiety led to a drastic reduction of the antiparasitic activity.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…15 The best IC 50 value for the inhibition of P. falciparum was 0.4 µM, thus achieving a remarkable improvement with respect to other inhibitors of PLM II. [8][9][10][11] We also demonstrated that the removal of the Lys-PQ moiety led to a drastic reduction of the antiparasitic activity.…”
Section: Introductionmentioning
confidence: 68%
“…[9][10][11] Considering the redundancy of PLMs, 12,13 it is therefore necessary to design compounds able to inhibit two or more in this enzyme family in order to develop drugs active on P. falciparum. Some of the synthesized compounds, designed as PLM II inhibitors, are also strong inhibitors of PLM I, which is, in view of the recent literature, a prerequisite for developing new antimalarial agents.…”
Section: Discussionmentioning
confidence: 99%
“…13,18,19 However, knockout experiments have shown that the DV plasmepsins and falcipains 2 and 2′ are individually not essential to parasite survival, and because of this redundancy between the function of these enzyme classes it has proved difficult to develop drugs that effectively block the digestive process within the DV. [21][22][23][24] Peptides produced in the DV may be further processed to dipeptides by a dipeptidyl aminopeptidase I, an orthologue of mammalian cathepsin C. 25,26 Small peptides and dipeptides may also be reduced to free aminoacids within the DV and/or transported to the parasite cytosol for processing by aminopeptidases. 20,[27][28][29][30][31][32][33] Aminopeptidases are essential in releasing aminoacids from haemoglobin-derived peptides and are thus central to the growth and development of malaria parasites in the erythrocyte.…”
Section: -16mentioning
confidence: 99%
“…PfPMT was found to be expressed in the clinical strain of the parasite and can be a potential point of therapeutic intervention. Plasmepsins I and IV, involved in hemoglobin degradation, are already present in the ring stages of Pf, indicating that hemoglobin degradation begins early in the parasite life cycle and is a promising step for therapeutic intervention [29,30]. Pf is also known to rely heavily on de novo polyamine biosynthesis [31].…”
Section: S-adenosyl Homocysteinasementioning
confidence: 99%